2016
DOI: 10.1371/journal.pone.0162603
|View full text |Cite
|
Sign up to set email alerts
|

Decreased β-Cell Function Is Associated with Reduced Skeletal Muscle Mass in Japanese Subjects without Diabetes

Abstract: BackgroundDecreased insulin secretion has a great impact on the incidence of type 2 diabetes in Japanese subjects. It is not clear whether β-cell function is related to muscle mass in subjects without diabetes. We investigated the relationship between β-cell function and skeletal muscle mass in Japanese subjects without diabetes.MethodsThe study included 1098 subjects (538 men and 560 women) aged 40 to 79 years, without diabetes (fasting glucose lower than 126 mg/dL and glycosylated hemoglobin lower than 6.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…For example, in a study on patients with type I diabetes, the PV was lower for insulin-dependent diabetic patients than for normal subjects [26], suggesting that reduced PV is associated with β-cell dysfunction. Additionally, a study on the association between sarcopenia and the clinical parameters of β-cell function and insulin resistance revealed that reduced β-cell function is associated with reduced skeletal muscle mass in subjects without diabetes [27]. We used CT images to measure the PV; thus, pathological changes, such as reduced β-cell function in the pancreas, could not be directly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study on patients with type I diabetes, the PV was lower for insulin-dependent diabetic patients than for normal subjects [26], suggesting that reduced PV is associated with β-cell dysfunction. Additionally, a study on the association between sarcopenia and the clinical parameters of β-cell function and insulin resistance revealed that reduced β-cell function is associated with reduced skeletal muscle mass in subjects without diabetes [27]. We used CT images to measure the PV; thus, pathological changes, such as reduced β-cell function in the pancreas, could not be directly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of Japanese men and women aged 40–79 years without diabetes showed a significant positive correlation between appendicular muscle mass index and clinical parameters of both β-cell function and insulin resistance. 20 …”
Section: Discussionmentioning
confidence: 99%
“…T2D is the most common type of diabetes with prevalence in Taiwan. T2D begins with insulin resistance in which cells fail to respond to and uptake of insulin in the body [ 114 116 ]. Insulin resistance can be enhanced by weight reduction and exercise [ 117 ].…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%